Physical Insights on MILD Combustion From DNS - Swaminathan, N. (Frontiers in Mechanical Engineering, 2019)
MILD combustion is gaining interest in recent times because it is attractive for “green” combustion technology. However, its fundamental aspects are not well understood. Recent progresses made on this topic using direct numerical simulation data are presented and discussed in a broader perspective. It is shown that a revised theory involving at least two chemical timescales is required to describe the inception of this combustion not only showing both autoignition and flame characteristics but also a strong interaction between these two phenomena. The reaction zones have complex morphological and topological features and the most probable shape is pancake-like structure implying micro-volume combustion under MILD conditions unlike the sheet-combustion in conventional cases. Relevance of the MILD (micro-volume) combustion to supersonic combustion is explored theoretically and qualitative support is shown and discussed using experimental and numerical Schlieren images.